Movement behaviours, breakfast consumption, and fruit and vegetable intake among adolescents - Sampasa-Kanyinga, Hugues; Hamilton, Hayley A.; Chaput, Jean-Philippe (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background It is recommended that children and adolescents spend ≥ 60 min per day of moderate-to-vigorous physical activity, ≤ 2 h per day of recreational screen time, and 9–11 h of sleep per night for school-aged children or 8–10 h per night for adolescents. The objective of this study was to examine the associations of compliance with physical activity, screen time, and sleep duration recommendations with the frequencies of breakfast consumption and fruit and vegetable intake among adolescents. Methods Data from a cross-sectional and province-wide survey of students in grades 7–12 in Ontario (Canada) were used for this analysis (n = 12,759 students; 15.2 ± 1.8 years; 56% females). Movement behaviours and eating habits were self-reported. Multivariable ordered logistic regression analyses were adjusted for age, sex, ethnoracial background, subjective socioeconomic status, and body mass index z-score. Results Compliance with all three recommendations was associated with more frequent breakfast consumption (OR: 2.77; 95% CI: 2.17–3.55) and fruit and vegetable intake (OR: 2.95; 95% CI: 2.41–3.62) compared with compliance with none of the recommendations. Compliance with the different combinations of recommendations was also associated with more frequent breakfast consumption and fruit and vegetable intake, with some exceptions. There was a dose–response gradient between the number of recommendations met (3 > 2 > 1) and more frequent breakfast consumption (p < 0.001) and fruit and vegetable intake (p < 0.001), with compliance with all three recommendations being the best combination. Conclusions These findings suggest that compliance with the physical activity, screen time, and sleep duration recommendations is associated with more frequent breakfast consumption and fruit and vegetable intake among adolescents.